2007
DOI: 10.1111/j.1600-079x.2007.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of insulin and IGF‐1 signaling pathways by melatonin through MT1 receptor in isolated rat pancreatic islets

Abstract: Melatonin diminishes insulin release through the activation of MT1 receptors and a reduction in cAMP production in isolated pancreatic islets of neonate and adult rats and in INS-1 cells (an insulin-secreting cell line). The pancreas of pinealectomized rats exhibits degenerative pathological changes with low islet density, indicating that melatonin plays a role to ensure the functioning of pancreatic beta cells. By using immunoprecipitation and immunoblotting analysis we demonstrated, in isolated rat pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 60 publications
4
78
0
17
Order By: Relevance
“…This concept gives emphasis to the presence of a circadian regulation over pancreatic function. The analysis of melatonin on pancreatic islet by immunoprecipitation and immunoblotting shown that melatonin regulate growth and differentiation of pancreatic cells by stimulating insulin growth factor receptor (IGF-R) and insulin receptor (IR) tyrosine phosphorylation (69). It activates two intracellular signaling pathways: PI3K/AKT (involved with cell metabolism) and MEK/ERKs (involved in cell proliferation, growth and differentiation) (69).…”
Section: Melatonin and Insulin Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept gives emphasis to the presence of a circadian regulation over pancreatic function. The analysis of melatonin on pancreatic islet by immunoprecipitation and immunoblotting shown that melatonin regulate growth and differentiation of pancreatic cells by stimulating insulin growth factor receptor (IGF-R) and insulin receptor (IR) tyrosine phosphorylation (69). It activates two intracellular signaling pathways: PI3K/AKT (involved with cell metabolism) and MEK/ERKs (involved in cell proliferation, growth and differentiation) (69).…”
Section: Melatonin and Insulin Secretionmentioning
confidence: 99%
“…The analysis of melatonin on pancreatic islet by immunoprecipitation and immunoblotting shown that melatonin regulate growth and differentiation of pancreatic cells by stimulating insulin growth factor receptor (IGF-R) and insulin receptor (IR) tyrosine phosphorylation (69). It activates two intracellular signaling pathways: PI3K/AKT (involved with cell metabolism) and MEK/ERKs (involved in cell proliferation, growth and differentiation) (69). Moreover, the decrease in melatonin levels augmented insulin secretion in rats during the day while at the time of night, low levels of insulin along with high glucose levels are measured when melatonin levels are elevated (70,71).…”
Section: Melatonin and Insulin Secretionmentioning
confidence: 99%
“…Growth hormone resistance and reduced insulin and IGF-1 signaling extend the mouse lifespan (192). An effect of melatonin on the IIS pathway via the MT 1 receptor has been identified in rat pancreatic islet cells (193), and MT 1 downregulation leads to insulin resistance (194). Melatonin can improve insulin resistance via alteration of pancreatic gene expression in male mice (195).…”
mentioning
confidence: 99%
“…кроме того, в отсутствие мелатонина наруша-ется функция инсулиновых рецепторов, в част-ности МТ2 в адипоцитах жировой ткани, что резко снижает захват глюкозы этими клетками [60,61]. Выявленные эффекты пинеалэктомии исчезали в результате терапии мелатонином [62,63]. Таким образом, эпифизарный мелато-нин необходим для синтеза, секреции и реали-зации функций инсулина.…”
unclassified